Faktor Penerimaan Media Sosial Instansi Pemerintah di Indonesia - Suryadharma, Bertung; Susanto, Tony Dwi (INTEGER: Journal of Information Technology, 2017)
The presence of social media has a huge impact on life today. Social media get a special place on internet usage in Indonesia. As much as 87.4% of internet usage in Indonesia is used by the community to access social media. Government agencies in Indonesia have slowly utilized social media as a means of communication with the community. The concern is that social media users in Indonesia are very large, but public participation on government social media accounts is still low. This study aims to find out the causes or factors that influence public participation on government social media accounts that have never been studied previously. The study is based on literature studies and empirical studies to find the factors that influence public participation on government social media accounts. This research proposed a research model with six variables that represent factors influencing public participation to participate with government social media. Furthermore, the relationship between variables will be validated using the Structural Equation Model (SEM) -PLS method. The object of this research is the community that has become a participant on the government's social media account.The results of this study state that five out of six variables have proven to influence community participation to participate with the social media of the government. Keywords: social media, government, participation